PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 187 PEKANBARU - Desca Alestaria; Hendri Marhadi; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purposes of research were to improve student’s study result of social sciences by implementation cooperative learning Scramble type.The background of the problem in this research was the poor students’ achievements in social sciences, it can be seen on students’ social sciences scores. There were 20 of 35 students who had not achieved the Achievement Standard (57,14%), while the ones who achieved were only 15 students (42,85%), and the average scores of the class was 64,42. The Achievement Standard that school determines is 70. The method of research was classroom action research implemented in two cycles that consist of planning, action, observation, and reflection. Data were collected by observation technigue, test technigue and documentary technigue. The instrument of data collection used observation sheet and test student’s result . At the first meeting in cycle I, the percentage of teachers’ activity was 62.50% which is categorized as good. At the second meeting, the percentage increased to 75.00% which is categorized as good. At the first meeting in cycle I, the percentage increased to 87.50% that is categorized as very good. At the second meeting the percentage increased to 95.83% which is categorized as very good. The students’ activities had increased. At the first meeting in cycle I, the students’ activities gained 58.33% which is categorized as enough, while at the second meeting in cycle I the students’ activities gained 70.83% which is categorized as good.At the first meeting of cycle II, the percentage increased to 83.33% that is categorized as very good, while at the second meeting the percentage increased to 91.67% which is categorized as very good. The average of students’ achievements before the implementation cooperative learning student facilitator and explaining type was 64,42 which increased to 73,57 in cycle I, and increased again to 84,14 in cycle II. The result of research showed that implementation cooperative learning Scramble type can improve student’s result of social sciences.Key Words: Study Result,Cooperative Learning Scramble Type, social sciences